PERBANDINGAN PENAMBAHAN PELATIHAN MOBILISASI SARAF DENGAN MYOFASCIAL RELEASE PADA ACTIVE ISOLATED STRETCHING TERHADAP PENINGKATAN FLEKSIBILITAS OTOT HAMSTRING PADA MAHASISWA PROGRAM STUDI FISIOTERAPI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - I Nyoman Oka Yuliartha; Dedi Silakarma; Nyoman Agus Bagiada (E-Jurnal Medika Udayana, 2017)
Flexibility is an ability of tissue or muscle for stretching to the maximum , this enables thebody to move in full joint movement scope without experiencing any pain. There are occurrencesin the community when the hamstring muscle flexibility was reduced. This will affect the balanceof muscle contraction, posture changes, and disturbances in walking, joint stiffness, capsule andtendon disorders. To overcome this problem proper stretching is needed. The purpose of this studywas to determine the difference between the training using active isolated stretching and nervemobilization with the training using active isolated stretching and myofascial release in increasingthe hamstring muscle flexibility. This research is an experiment research design with pre and posttest control group design. These samples included 22 people who were divided into two groups.Group 1 was given training using active isolated stretching and nerve mobilization, while Group 2was given the training using active isolated stretching and myofascial release. Hamstring muscleflexibility measurement was conducted through sit-and-reach test to obtain preeliminary dataISSN:2303-1395 E-JURNAL MEDIKA,VOL 6 NO 9,SEPTEMBER 2017http://ojs.unud.ac.id/index.php/eum(before training) and final data (after training).In the Group 1 showed p = 0.000 with a meandifference 5,222±1,092, while in Group 2 showed p = 0.000 with a mean difference 4,222±1,394.The results showed there was a significant decrease in pain in each group. At different test betweenGroup 1 and Group 2 using independent sample t-test was obtained p = 0,110 (p> 0.05). Based onthese results, it can be concluded that the training using active isolated stretching and nervemobilization showed no difference as the training using active isolated stretching and myofascialrelease in increasing the hamstring muscle flexibility.Keywords: Flexibility, active isolated stretching, nerve mobilization, myofascial release, sit andreach test